Entrapment neuropathies: challenging common beliefs with novel evidence - Schmid, A; Hailey, L; Tampin, B (Journal of Orthopaedic and Sports Physical Therapy, 2018)
Entrapment neuropathies are the most prevalent type of peripheral neuropathy and often a challenge to diagnose and treat. To a large extent, our current knowledge is based on empirical concepts and early (often biomechanical) studies. This Viewpoint will challenge some of the current beliefs with recent advances in both basic and clinical neurosciences. J Orthop Sports Phys Ther 2018;48(2):58-62. doi:10.2519/jospt.2018.0603.